"Cold" Cognitive Control and Attentional Symptoms in Anxiety: Perceptions Versus Performance. Issue 6 (November 2019) - Hallion, Lauren S.; Tolin, David F.; Billingsley, Amber L.; Kusmierski, Susan N.; Diefenbach, Gretchen J.
Abstract: Clinically significant anxiety is associated with an array of attentional symptoms (e.g., difficulty concentrating; unwanted thought) that are subjectively experienced as severe. However, neuropsychological findings are mixed with respect to the presence of cognitive deficits that can account for these symptoms. Contextualizing predictions from established clinical theories (e.g., Attentional Control Theory) within contemporary, neurobiologically derived models of cognitive control (Dual Mechanisms of Control Theory), the present study investigated the relationship between "cold" proactive and reactive cognitive control, task effort, and subjective attentional symptoms (difficulty concentrating; unwanted thought) in a mixed clinical sample of individuals with generalized anxiety disorder (GAD) and/or obsessive-compulsive disorder (OCD) and a comparison sample of healthy controls. Clinical status moderated the relationship between attentional symptoms (attentional focusing and trait worry) and proactive cognitive control response time. Clinical status also moderated the relationship between trait worry and task effort. Higher trait worry was associated with slower proactive control and lower effort in healthy participants, but faster proactive control in clinical participants. Self-reported attentional focusing showed differential validity vis-à-vis proactive control response time in clinical versus healthy participants. Post-hoc conditional effects analysis suggested more accurate self-appraisals in healthy controls, but was not significant after correction for multiple comparisons. Preliminary evidence suggested that differences in task effort in anxious versus healthy adults may relate to subjective attentional symptoms in GAD and OCD. Highlights: Clinical anxiety (GAD/OCD) is associated with subjective attentional impairment Cognitive control task performance was intact in anxiety despite symptoms Trait worry and focusing related to task performance differentially by group Findings were specific to proactive cognitive control Differences in task effort may help to account for this discrepancy